2014
DOI: 10.4103/0976-0105.141948
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of antibiotic resistance pattern to urinary pathogens in a Tertiary Care Hospital in South India

Abstract: Context:The distribution of uropathogens and their susceptibility pattern to antibiotics vary regionally and even in the same region, they change over time. Therefore, the knowledge on the frequency of the causative microorganisms and their susceptibility to various antibiotics are necessary for a better therapeutic outcome.Aim:The aim was to study the frequency and distribution of uropathogens and their resistance pattern to antibiotics in a tertiary care hospital.Settings and Design:Retrospective study for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
27
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 6 publications
10
27
2
Order By: Relevance
“…This is consistent with other studies. (20)(21)(22)(23)(24) UTI is more common in females than in males, as female urethra structurally found less effective for preventing the bacterial entry. (25) It may be due to the proximity of the genital tract and urethra and adherence of urothelial mucosa to the mucopolysaccharide lining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with other studies. (20)(21)(22)(23)(24) UTI is more common in females than in males, as female urethra structurally found less effective for preventing the bacterial entry. (25) It may be due to the proximity of the genital tract and urethra and adherence of urothelial mucosa to the mucopolysaccharide lining.…”
Section: Discussionmentioning
confidence: 99%
“…(31) to 98%. (20) In this study the resistance results were Amoxiclav (62.9%), Amikacin (32.3%), Nalidixic acid (51.4%) and Norfloxacin (48.6%). In a similar study, Somashekara SC et al showed the antibiotic resistance pattern of Klebsiella pneumonia to be Amoxiclav (68%), Amikacin (26%), Nalidixic acid (48.2%) and Norfloxacin (38%).…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] In Somasekara et al 13 study, highest resistance of E. coli was seen towards ciprofloxacin and ceftazidime (72% and 58% respectively). Cotrimoxazole resistance was also 68.8% whereas only 8% were imipenem resistant.…”
Section: Comparison Of Percentage Of Uropathogens Isolated In the Prementioning
confidence: 99%
“…A very recent study from India showed high level (80%) of expression of efflux pumps specific to antimicrobial agents indicates antimicrobial resistance [22]. E. coli cultures isolated from urinary samples showed a high level of resistance to β-lactam and fluoroquinolones in recent study from South India [23]. The surveillance data show the highest resistance pattern of antimicrobial agents in E. coli that have been used from the long time in human medicine [24].…”
Section: Introductionmentioning
confidence: 99%